DEVELOPMENT OF AUGMENTED REALITY (AR) INTERACTIVE STORYBOOK “BERSIH DIRI BERSAMA MARE” BASED ON ANDROID TO STIMULATE MOTOR DEVELOPMENT OF CHILDREN AGED 4-5 YEARS - Putri Eka Mawardani, Irmala; Sutama, I Wayan; Astuti, Wuri (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2021)
Media storybooks based on Augmented Reality can be used by teachers to stimulate motor development about personal hygiene in children aged 4-5 years. The purpose of this research is to produce Augmented Reality interactive storybook media products that are validly tested by media and material experts with categories, effective, efficient and interesting in their use. The type of research used in this research is the type of Research & Development (R and D) research. The assessment criteria are aspects of efficiency, effectiveness and attractiveness. The instrument of quantitative data analysis technique was obtained from the validity of media experts and material experts. The results of accumulated validity from several experts yield a percentage of 97.75% which means it is very feasible to use. The trial used small groups and large group tests with the criteria for assessing effectiveness, efficiency and attractiveness with the results of 87.7%. The accumulation of data from the results of expert validation and group trials was 91.5%, which means that the media is feasible to use. Quantitative data was obtained from the results of interviews with kindergartens in Blitar. The researcher found that the interactive augmented reality storybook about self-cleaning with mare had three eligibility criteria, namely being effective, efficient and attractive to stimulate motor development about personal hygiene in children aged 4-5 years.